Assessment of Development Results - Tanzania - United Nations Development Programme (United Nations, 2015)
The Assessment of Development Results (ADR) for Tanzania was conducted by the Independent Evaluation Office of the United Nations Development Programme (UNDP) in 2014. The ADR for Tanzania examines the UNDP Tanzania country programme for the periods 2007-2010/2011 and 2011-2015/2016. In accordance with the evaluations terms of reference, UNDP’s contribution in Tanzania was assessed in seven programmatic cluster areas based on the thematic breakdowns of the country programmes under the review periods as well as the team configuration of the current office: Capacity Development; Democratic Governance; Private Sector Development; HIV/AIDS; Crisis Prevention and Recovery; Environment and Natural Resource Management; and Energy and Climate Change. The annual programme budget of the Tanzania country office was US25 million at the start of the period 2007-2010/11 (2007) and US28 million as of 2013, with a significant fluctuation in-between with the availability of external resources for specific programmes.